Inpatient blood glucose management of diabetic patients in a large secondary hospital - Daniel G. van Zyl; Paul Rheeder (South African Family Practice)
Background: Diabetes has become a major health problem worldwide, as well as in South Africa. This, coupled with the chronicity of the disease, relate to an increasing burden on health care facilities and an increasing number of hospital admissions of patients suffering from diabetes. Admissions are mostly related to diabetes itself, but the frequency of admissions for problems not related to diabetes is increasing as the prevalence of diabetes increases in the population. Proper inpatient glycaemic management is important for improving patient outcome and for reducing the risk of inpatient complications.